Exploring the Gap of English Learning Motivation in Chinese Ethnic Minority High School Students Through Critical Reading - Wen Jia; Huang Tao; Liao Qiang; Zhao Yaling; Kou Xinlong; Wan Jiahua (Jurnal Gramatika, 2024)
The motivation behind language learning, particularly in English as a Foreign Language (EFL), has garnered significant attention in China's second language acquisition landscape as a minority language. While extensive research has been conducted over the last few decades exploring motivation factors across various educational stages, such as early childhood, primary, junior high, and high school education, there remains a notable gap concerning the motivation of Chinese learners in high school, particularly in the realm of critical reading. This study addresses this gap through a qualitative case study, aiming to uncover the impact of learning experiences on the motivation of three Chinese ethnic students in senior high school. These students navigate a complex linguistic landscape, proficient in their mother tongue, Mandarin, and concurrently learning English as a foreign language. The intricacies of their social and cultural exposure contribute to the complexity of their English learning journey. Semi-structured interviews with the three participants shed light on the intricacies of their English learning motivation, revealing a predominant focus on examination-driven incentives. The study identifies significant influencers on motivation, including teachers' teaching styles, peers' attitudes toward English, and the overall learning atmosphere in the class. These findings affect educational policy-making and English instruction, particularly in Chinese ethnic regions. With the multifaceted nature of motivation in these specific contexts, educators and policymakers can tailor strategies that address the unique challenges faced by Chinese ethnic learners in high school, emphasizing the importance of a holistic and supportive language learning environment.